Determination of the Thermophysical Properties of Tuna Using the Heat Pulse Method - Ho Thi My Phong; Lu Thi Mong Thy; Hoang Thi Nam Huong; Do Huu Hoang (The Indonesian Institute of Science and Technology Research, 2025)
Although the tuna industry plays an important role in supporting the economy and local communities, it remains underdeveloped and faces several challenges, according to reports from the Ministry of Industry and Trade and the Vietnam Tuna Association. This study focuses on examining the heat-related physical properties of tuna—specifically, how well it conducts heat (thermal conductivity), how quickly heat spreads through it (thermal diffusivity), and how much heat it can store (specific heat capacity). These properties were measured using the heat pulse method within a temperature range of -15°C to 20°C. The results showed that thermal conductivity ranged from 0.394 to 1.103 W/m·K, thermal diffusivity from 1.11×10⁻⁸ to 2.60×10⁻⁷ m²/s, and specific heat capacity from 3,377.21 to 52,948.54 J/kg·K.